The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s00436-005-0037-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of Crotalus durissus terrificus and Bothrops jararaca venoms on Giardia duodenalis trophozoites

Abstract: Considering the snake venoms' pharmacological properties and chemotherapeutic potential as well as the need for new alternatives for Giardia infection treatment, the present study was carried out aiming to evaluate the in vitro effects of crude Crotalus durissus terrificus and Bothrops jararaca venoms on the growth and adherence of Giardia duodenalis trophozoites. Trophozoites (10(6)) were exposed to serial twofold dilutions of C. durissus terrificus and B. jararaca venoms that ranged from 3.125 to 200 microg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The low toxicity of fraction V and of the PLA 2 homologue isolated from fraction VI compared with the venom indicates their low overall toxicity in mice and reinforces the concept that these fractions are good lead compounds in the search for antimalarial activity. This is in agreement with reports on the use of snake venom PLA 2 s to inhibit microorganisms, such as bacteria and fungi, as well as parasites including Giardia duodenalis , Trypanosoma cruzi , Leishmania spp and P. falciparum [17,30,31,50,51,52]. …”
Section: Resultssupporting
confidence: 91%
“…The low toxicity of fraction V and of the PLA 2 homologue isolated from fraction VI compared with the venom indicates their low overall toxicity in mice and reinforces the concept that these fractions are good lead compounds in the search for antimalarial activity. This is in agreement with reports on the use of snake venom PLA 2 s to inhibit microorganisms, such as bacteria and fungi, as well as parasites including Giardia duodenalis , Trypanosoma cruzi , Leishmania spp and P. falciparum [17,30,31,50,51,52]. …”
Section: Resultssupporting
confidence: 91%
“…In the present study, all honeys tested against E. histolytica have shown varying in vitro trophozoiticidal activity. These results coincide with similar studies performed by other authors on the antiprotozoal activity of natural products (Khan et al, 2000, Shinohara et al, 2006, Almeida et al, 2007, Li et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…In particular, they include phospholipases A2 [6], L-amino acid oxidases [7] and cathelicidins [8]. Venoms of several snake species were shown to be toxic to protozoans [9][10][11][12] and identification of proteins manifesting anti-protozoan activity in viperid venoms revealed that phospholipase A2 [22], metalloproteinase [23], L-amino acid oxidase [24] and disintegrin [14] are toxic to different protozoa. For example, BnSP-7 toxin, a catalytically inactive phospholipase A2 from Bothrops pauloensis snake venom, showed activity against promastigote Leishmania amazonensis parasite forms, inhibiting parasite proliferation by 60-70% at toxin concentrations of 50-200 µg/mL 96 h after treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that phospholipases A2 [6], L-amino acid oxidases [7] and cathelicidins [8] possess antimicrobial properties. There are also some data about the influence of snake venoms on protozoa [9,10]. Recently the in vivo and in vitro antileishmanial activity of krait Bungarus caeruleus [11] and cobra Naja oxiana [12] venoms was demonstrated.…”
Section: Introductionmentioning
confidence: 99%